Methylphosphonic acid, CH3PO(OH)2 - Hans Reuter (Acta Crystallographica Section E, 2014)
The asymmetric unit of the title compound, CH5O3P, contains two independent molecules with nearly identical bond lengths and angles. In the crystal, each of the molecules acts as acceptor (P=O) and donor (P—OH) of four hydrogen bonds to three adjacent molecules, resulting in the formation of two different bilayers (one for each molecule) stacked perpendicular to the a axis in the crystal.